Politicians: be killed or survive - Bruno S. Frey; Benno Torgler (Center for Economic Studies and ifo Institute (CESifo), 2008)
In the course of history, a large number of politicians have been assassinated. Rational choice hypotheses are developed and tested using panel data covering more than 100 countries over a period of 20 years. Several strategies, in addition to security measures, are shown to significantly reduce the probability of politicians being attacked or killed: extended institutional and governance quality, democracy, voice and accountability, a well functioning system of law and order, decentralization via the division of power and federalism, larger cabinet size and strengthened civil society. There is also support for a contagion effect.
Keywords: D01; D70; K14; K42; Z10; 330; Assassinations; rational choice; governance; democracy; dictatorship; deterrence; protection; Politische Gewalt; Rationales Verhalten; Politisches System; Governance-Ansatz; Innere Sicherheit; Politische Stabilität; Welt